Expression of polycystic ovary syndrome candidate genes in bovine fetal and adult ovarian somatic cells - Menghe Liu; Katja Hummitzsch; Nicole A Bastian; Monica D Hartanti; Helen F Irving-Rodgers; Richard A Anderson; Raymond J Rodgers (Bioscientifica, 2022)
Polycystic ovary syndrome (PCOS) is an endocrine metabolic disorder that appears to have a genetic predisposition and a fetal origin. The fetal ovary has two major somatic cell types shown previously to be of different cellular origins and different morphologies and to differentially express 15 genes. In this study, we isolated the somatic gonadal ridge epithelial-like (GREL) cells (n = 7) and ovarian fetal fibroblasts (n = 6) by clonal expansion. Using qRT-PCR, we compared the gene expression levels of PCOS candidate genes with previous data on the expression levels in whole fetal ovaries across gestation. We also compared these levels with those in bovine adult ovarian cells including fibroblasts (n = 4), granulosa cells (n = 5) and surface epithelial cells (n = 5). Adult cell types exhibited clear differences in the expression of most genes. In fetal ovarian cells, DENND1A and ERBB3 had significantly higher expression in GREL cells. HMGA2 and TGFB1I1 tended to have higher expression in fetal fibroblasts than GREL cells. The other 19 genes did not exhibit differences between GREL cells and fetal fibroblasts and FBN3, FSHB, LHCGR, FSHR and ZBTB16 were very lowly expressed in GREL cells and fibroblasts. The culture of fetal fibroblasts in EGF-containing medium resulted in lower expression of NEIL2 but higher expression of MAPRE1 compared to culture in the absence of EGF. Thus, the two fetal ovarian somatic cell types mostly lacked differential expression of PCOS candidate genes.